DESIGNING THE CONTENT OF VOCATIONAL EDUCATION BY ANALYZING THE PROFESSIONAL WORK OF THE FUTURE EXPERT - Leonid B. Ershteyn (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The article considers principle of inversion, as the basic principle of detection of the content of vocational education, the essence of the principle is to analyze the relevance of certain elements of education in professional activity are encouraged to consider only those elements of the content that is actually required in professional activities. As a result, proposed a specific algorithm to identify the necessary and unnecessary elements of the content of vocational education, based on the results of the use of which then formed the content of disciplines taught in vocational education, in this particular specialty. Consider an example of using this algorithm, with the development of the content of a particular discipline